2016
DOI: 10.1371/journal.pone.0161248
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Developing Deprescribing Guidelines: Using Evidence and GRADE to Guide Recommendations for Deprescribing

Abstract: BackgroundClass specific deprescribing guidelines could help clinicians taper and stop medications no longer needed or which may be causing more harm than benefit. We set out to develop methodology to create such guidelines using evidence-based methods for guideline development, evidence synthesis and recommendation rating.Methods and FindingsUsing a comprehensive checklist for a successful guideline enterprise, we conducted a national modified Delphi consensus process to identify priorities for deprescribing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 36 publications
1
95
0
2
Order By: Relevance
“…Additionally, guidelines for safe methods of deprescribing cardiovascular medications are also needed; guidelines for deprescribing other medication classes have been developed and could provide a useful starting point. [24][25][26] We found that barriers to deprescribing were diverse but consistent across specialties and largely consistent with prior surveys of primary care physicians' perspectives on deprescribing PIMs. 9,10,12 Importantly, interfering with another clinician's treatment plan was the most frequently reported barrier to deprescribing cardiovascular medications, extending observations from other countries.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Additionally, guidelines for safe methods of deprescribing cardiovascular medications are also needed; guidelines for deprescribing other medication classes have been developed and could provide a useful starting point. [24][25][26] We found that barriers to deprescribing were diverse but consistent across specialties and largely consistent with prior surveys of primary care physicians' perspectives on deprescribing PIMs. 9,10,12 Importantly, interfering with another clinician's treatment plan was the most frequently reported barrier to deprescribing cardiovascular medications, extending observations from other countries.…”
Section: Discussionsupporting
confidence: 79%
“…Tools like the Screening Tool of Older Persons Prescriptions in Frail Adults With Limited Life Expectancy could assist clinicians with identifying cardiovascular medications that provide limited benefit. Additionally, guidelines for safe methods of deprescribing cardiovascular medications are also needed; guidelines for deprescribing other medication classes have been developed and could provide a useful starting point …”
Section: Discussionmentioning
confidence: 99%
“…19 Currently, deprescribing guidance is limited, with clinicians reporting difficulty in weighing the harms against the benefits of continuing or stopping medications. 29 PPIs were selected by OPEN as 1 of 3 medications for development of a deprescribing guideline to "support health care professionals taper or stop potentially inappropriate medications that may be causing harm or no longer providing a benefit as well as monitoring for potential adverse withdrawal effects". 28 At the time of the current study (late 2015 to early 2016), the OPEN algorithm had not yet been published.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the methodology for developing the OPEN deprescribing algorithms has been published (in August 2016). 29 Thompson and others 27 implemented and evaluated the OPEN PPI deprescribing algorithm at 3 residential care sites and found that it could decrease PPI prescribing. We used the algorithm to assess whether residents fit the criteria for discontinuation and then monitored those with PPI discontinuation to assess for recurrent gastrointestinal symptoms that would warrant re-initiation of the PPI.…”
Section: Discussionmentioning
confidence: 99%
“…The target medication is stopped and health outcomes are measured. These types of studies are essential for the development of drug-specific deprescribing guidelines [12] to provide guidance on when it is suitable to withdraw medications. They also have the benefit of measuring drug-specific outcomes including resolution of adverse effects or reduction of risk (e.g.…”
Section: Deprescribing Studiesmentioning
confidence: 99%